Are long-term health effects on the musculoskeletal system to be expected from Olympic wrestling? - Diezemann, E. D. (International Journal of Wrestling Science, 2023)
The quote: "Great sport begins where it has long stopped being healthy" by Bertold Brecht, German dramatist, poet and storyteller is now irrefutable in sports medicine. We know that high-performance sports can lead to late damage to the motor apparatus. To what extent does this apply to Olympic Wrestling? Wrestling is one of the oldest forms of sports. Wrestling matches were held even in ancient Egypt around 3999 B.C. It was part of the program in the Olympic Games of antiquity and has remained so to the present summer games. Wrestling demands of the athletes appropriate condition combined with a high level of reactions and speed. This is impossible without a healthy cardiovascular system, healthy metabolism and a healthy motor apparatus. This results to a high level of sports-specific stress in the course of a wrestling career. Can this lead to irreversible late damage?